Analysis of Internal and External Microorganism Community of Wild Cicada Flowers and Identification of the Predominant Cordyceps cicadae Fungus - Huang, Ailin; Wu, Tao; Wu, Xiuyun; Zhang, Biao; Shen, Yuanyuan; Wang, Suying; Song, Wenjun; Ruan, Haihua (Frontiers in Microbiology, 2021)
The parasitoid fungus Cordyceps cicadae, whose fruiting bodies are known in China as “chan hua”, literally “cicada flower”, has been used as a traditional Chinese medicinal ingredient for centuries. However, systematic disclosure of the vital factors responsible for the formation of wild cicada flower is limited. Here, we determined the physicochemical properties of soil and simultaneously analyzed the diversities and the structures of microbial community inhabiting the coremia, sclerotia and soil around wild cicada flowers through high-throughput sequencing. Our results indicated that cicada flower more preferentially occurred in acidic soil (pH 5.9) with abundant moisture content (MC), total nitrogen (TN), and organic matter (OM). The dominant fungal genera in soil mainly included Isaria, f__Clavariaceae_Unclassified, Umbelopsis, f__Chaetomiaceae_Unclassified, Mortierella, f__Sordariaceae_Unclassified and Arcopilus et al. Among them, Cordyceps cicadae was the only fungi that were massively detected both in coremia and sclerotia with abundance of 83.5% and 53.6%, respectively. Based on this, a Cordyceps cicadae strain named AH10-4 with excellent adenosine and N6-(2-hydroxyethyl)-adenosine (HEA) producing capability was successfully isolated. However, to the aspect of bacteria, Burkholderia-Caballeronia-Paraburkholderia, Bacillus, Acidibacter, f__Xanthobacteraceae_Unclassified and Candidatus_Solibacter were the dominant genera in soil. Pedobacter, f__Enterobacteriaceae_Unclassified, Pandoraea, Achromobacter, Stenotrophomonas, Burkholderia-Caballeronia-Paraburkholderia, and Chitinophaga were the dominant genera in coremia and sclerotia. Notably, Burkholderia-Caballeronia-Paraburkholderia was the shared bacteria among them with high abundance of 3.1%, 11.4% and 5.2% in sclerotia, coremia and soil respectively. However, the possible role of this bacteria to the occurrence of cicada flower has been unclear to our knowledge. By analyzing the correlation between physicochemical properties and microbial community of soil, we found that MC, Fe, and Zn were significantly negatively correlated with soil Isaria, and Cu was significantly negatively correlated with most dominant soil bacterial genera. But Mg was significantly positively correlated with most dominant taxa. This study provides new insight into the formation mechanisms of cicada flower and may contribute to the large-scale cultivation of cicada flowers.